Development of Building Maintenance E-Report System Using Building Information Modeling - M.SUOFIAN, FAZEERUL; ABDULLAH, MOHD SUFYAN; MOHAMED, JULIANA (Progress in Engineering Application and Technology, 2021)
The aim of this study is to produce the Building Maintenance e-Report system using Building Information Modelling (BIM) tools. In this study, the 3D model of one block of UTHM Pagoh staff block will be view using Autodesk 360 viewer. The experimental study is design to evaluate the effectiveness of the Building Maintenance e-Report system. Next, the project is carried out by create the database using Glide and create the 3D BIM model using Revit Software. A web-based is built for simulation of the system and 3D model. Last but not least, all the objectives are achieved after a simulation be made to show how to operate this UTHM Pagoh E-Maintenance Report system.